Clinical and reproductive consequences of using BVDV contaminated semen in artificial insemination in a beef herd in Argentina - Gonzalez Altamiranda, Erika Analia (2012)
The current report was prompted by an atypical outbreak of mucosal disease that occurred in a beef herd in the southwestern part of Buenos Aires Province, Argentina, where a total of 9/41 (21.9%) yearling bulls died. Blood samples from 73 bulls and 189 heifers were tested for evidence of persistent BVDV infection with Bovine Viral Diarrhea Virus (BVDV). Non-cytopathic BVDV was isolated from 7 (9.6%) 24- to 36-month-old bulls, and 3 (1.6%) 36-month-old heifers. Non-cytopathic BVDV was also detected in the seminal plasma of three of six persistently infected (PI) bulls. Furthermore, a 171 bp genomic fragment of BVDV was consistently detected by nested RT-PCR in one of the two samples of the commercial semen used for artificial insemination, indicating that this semen could be a possible source of infection for the whole herd. To evaluate the possible reproductive consequences of PI heifers and bulls, ovaries and semen were obtained from PI cattle for in vitro assays. The in vitro fertilization of oocytes with semen from PI bulls was associated with decreased cleavage and embryo development rates. Additionally, non-cytopathic BVDV was isolated from the follicular fluid of PI heifers. Genetic typing revealed that all isolates BVDV from the present study had a high percentage of homology and that all of the fragments from the RT-PCR clearly fit with the BVDV 1b cluster. These findings confirm the negative impact that BVDV can have on the reproductive performance of cattle and the importance of applying the proper sanitary controls to minimize the risk of BVDV infection.